Migrazione e letteratura (la stagione presente e viva): Миграциите и литературата (сегашно и живо време) - Gnisci, Armando; Gjurchinova, Anastasija (Identities: Journal for Politics, Gender and Culture, 2004)
Author(s): Armando Gnisci | Арманди Њиши Title (Italian): Migrazione e letteratura (la stagione presente e viva) Title (Macedonian): Миграциите и литературата (сегашно и живо време) Translated by (Italian to Macedonian): Anastasija Gjurchinova | Анастасија Ѓурчинова Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 3, No. 1 (Summer 2004) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 135-157 Page Count: 22 Citation (Italian): Armando Gnisci, “Migrazione e letteratura (la stagione presente e viva),” Identities: Journal for Politics, Gender and Culture, Vol. 3, No. 1 (Summer 2004): 135-157. Citation (Macedonian): Армандо Њиши, „Миграциите и литературата (сегашно и живо време)“, превод од италијански Анастасија Ѓурчинова, Идентитети: списание за политика, род и култура, т. 3, бр. 1 (лето 2004): 135-157.